The Need of Trusted Primary Care: Lesson Learnt from The COVID 19 Outbreak in Indonesia - Trevino Aristarkus Pakasi (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
Indonesia declared COVID 19 as an outbreak since March 2020, where the President of Indonesia announced the fist two cases who were cured already. Since then a lot of publication, as well as information, spread out through social media. The hoax buster of the government had already put 134 hoaxes in the website only in one month 1. Thus, one can imagine how difficult for Indonesian people to understand the situation of the outbreak and to properly respond to it. Cases increased exponentially and it was estimated that Indonesia would reach 20,000 cases at the end of March 2020 2. The fact is up till the 6th of April 2020, Indonesia reported 2,491 cases 3.What happens to the estimation? Was it wrong or a lot of underreported cases occur in the community? Is it because of the intervention that the government launched effectively?